Design of reconfigurable Patch Antenna with a Switchable V-Slot - Al-Maznaee, Tariq; Eldin Abdel-Raouf, Hany Essam (EMW Publishing, 2009)
In this paper we present the design of a novel Patch Antenna with Switchable V-Slot (PASVS) that resonates at two di®erent frequencies. The antenna operates at the lower frequency when the switch is OFF and at the higher frequency when the switch is ON. This antenna is designed for special applications which need small frequency ratio. The di®erent e®ects of the feeding position,slot location, and slot length are investigated in this paper. This investigation has been used to optimize the design of the PASVS antenna in terms of the return loss (RL), bandwidth, gain, and required frequency ratio.